If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54(20x + 12) = -35 Reorder the terms: 54(12 + 20x) = -35 (12 * 54 + 20x * 54) = -35 (648 + 1080x) = -35 Solving 648 + 1080x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-648' to each side of the equation. 648 + -648 + 1080x = -35 + -648 Combine like terms: 648 + -648 = 0 0 + 1080x = -35 + -648 1080x = -35 + -648 Combine like terms: -35 + -648 = -683 1080x = -683 Divide each side by '1080'. x = -0.6324074074 Simplifying x = -0.6324074074
| 4x+0.54=0.83-8.3x-0.33 | | 4x^2+5y^2+8x-20y+4=0 | | -5(3m+8)+4(m-4)= | | 81=7+b | | 6x+2(3x-9y+5)+(-9)=12x-18y+1 | | 1.25(20x+12)=-35 | | 5/13×t=-9 | | -20=25+3x | | 6/.02 | | h+367=285 | | (3x-9)/5=6 | | 2b^2-2b-5=0 | | -8x+1.4=9.4 | | x/1-9=-9 | | (5x-6)(x+10)=0 | | 75q=3756 | | -6x-6-7=-13 | | -2(x-9)=-34 | | 8b=96 | | 4k-5k-4k= | | 17g=981 | | 4x^3-2x^3= | | -5=q^7 | | 30=12x-4+10x-10 | | -14x=-336 | | 3x-9/5=6 | | .75z+6= | | 3(y-4)=(3y-5-4y)-(2-5y+10) | | 6.6g+4=4.6g+8 | | 75=3x+2+10x-5 | | 1/3-4/x=2-3/2x | | 7x-10+28+2x=-5 |